Implementation of video tutorial-assisted worksheets to improve the learning outcomes of junior high school students on environmentally friendly technology - Rini Yunita Rahman; Laifa Rahmawati; Salma Samputri (Jurnal Pendidikan Informatika dan Sains, 2026)
Effective learning requires innovative instructional media. This study aimed to determine (1) the improvement in learning outcomes following the implementation of video tutorial-assisted worksheets among students of SMP Nasional Makassar, and (2) whether there was a significant difference in learning outcomes before and after the implementation of video tutorial-assisted worksheets. This study employed a pre-experimental method with a one-group pretest-posttest design. The population comprised all ninth-grade students of SMP Nasional Makassar, totaling 179 students, from which a sample of 32 students was selected through purposive sampling. Learning outcomes were measured using a multiple-choice test that had been developed and validated prior to implementation. Data were analyzed descriptively and inferentially. The results showed that (1) learning outcomes improved, as indicated by an N-Gain of 0.51 (moderate category), and (2) there was a statistically significant difference between pretest and posttest scores after the implementation of video tutorial-assisted worksheets, as indicated by a significance value of less than 0.05. These findings demonstrate that worksheets combined with video tutorial media have a positive impact on the science learning process and help improve students’ understanding and learning outcomes.